Perancangan UI/UX pada Startup Suvis Indonesia Menggunakan Metode Lean UX Startup - Afif Fathurrahman; Tan Amelia; Tri Sagirani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Suvis Indonesia is a new startup that acts as an intermediary between consumers and electronic furniture technicians in providing household electronic furniture services. The current problem is that as a new startup, the company needs a User Interface (UI) and User Experience (UX) design as the basis for building a platform. Due to limited capital, the Suvis Indonesia startup must be run effectively and efficiently so that it prioritizes just in time production but still prioritizes the needs of its consumers. The solution used to solve the above problems is to design UI/UX using the Lean UX method. This method has the advantages of “Cost Saving, Time Saving, User-centric, and Data-driven”. Based on the analysis, implementation and evaluation resulted in a final prototype which is a combination of prototypes A and B which have been validated in terms of appearance, to criticism and suggestions from consumer users and technicians. Prototype A was selected for 6 features and Prototype B was selected for 6 features. In addition, this research produces a consistent user interface in terms of color, font, image/video and layout and user experience which is easy for users to understand to use the application and get information as needed